United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Stress Testing. (IMF Staff Country Reports; Country Report, 2010)
The stress testing analysis in the United States was based on publicly available information and on models that are subject to a considerable degree of uncertainty. The stress tests illustrate important vulnerabilities in the banking sector. It highlights the importance of macrofinancial linkages, and dependencies among the largest institutions. The results illustrate the high sensitivity of Bank Holding Company's asset quality and capital positions. Market liquidity risks appear to have declined, although financial firms remain vulnerable to funding rollover risk. The life insurance sector is relatively resilient.